1982
DOI: 10.1128/mcb.2.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the genetic locus for the structural gene and a new regulatory gene for the synthesis of repressible alkaline phosphatase in Saccharomyces cerevisiae.

Abstract: Two lines of evidence showed that the PH08 gene encodes the structure of repressible, nonspecific alkaline phosphatase in Saccharomyces cerevisiae: (i) the enzyme produced by a temperature-sensitive pho8 mutant at the permissive temperature (25°C) was more thermolabile than that of the wild-type strain, and (ii) the PH08 gene showed a gene dosage effect on the enzyme activity. The pho8 locus has been mapped on chromosome IV, 8 centimorgans distal to rna3. A new mutant carrying the pho9 gene was isolated which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Under the Pi-sufficient conditions, ALP activity by Pho8p was low, but detectable (Fig. 1b), as reported by Kaneko et al (1982). It has been reported that WT cells in the stationary phase subcultured in a fresh YPD medium increase their polyP content during the logarithmic and early stationary phases, but that the polyP content decreases soon afterwards (Werner et al, 2005).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Under the Pi-sufficient conditions, ALP activity by Pho8p was low, but detectable (Fig. 1b), as reported by Kaneko et al (1982). It has been reported that WT cells in the stationary phase subcultured in a fresh YPD medium increase their polyP content during the logarithmic and early stationary phases, but that the polyP content decreases soon afterwards (Werner et al, 2005).…”
Section: Discussionsupporting
confidence: 57%
“…These strains were grown at 30∞C under aerobic conditions in a YPD medium (1% yeast extract, 2% peptone and 2% glucose) or a low Pi YPD medium (YPD (-Pi)). The YPD (-Pi) medium was made according to a previously established method (Werner et al, 2005), which was based on the method of Kaneko et al (1982). Growth was measured by determining the optical density at 600 nm (OD 600 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Pho80p/Pho85p kinase pair negatively regulates the Pho4p transcription factor for the induction of phosphate uptake and storage genes such as PHO84 (Kaneko et al 1982;Ogawa et al 2000;Wykoff and O'shea 2001;Lee et al 2007;Wykoff et al 2007). We addressed whether hyperactive Pho4p in pho80 mutants accounts for the severe oxygen toxicity of sod1Δ pho80Δ cells.…”
Section: Resultsmentioning
confidence: 99%
“…Of the strains tested, the most severe oxygen toxicity was observed when phosphate control was disrupted through mutations in the phosphate-sensing kinase complex Pho80p/ Pho85p (Kaneko et al 1982;Ogawa et al 2000;Wykoff and O'shea 2001;Carroll and O'shea 2002;Lee et al 2007;Wykoff et al 2007). Deletion of either pho80 or pho85 rendered sod1Δ mutants lacking Cu/Zn SOD1 inviable in air and cells seemed nearly devoid of Mn antioxidant protection (Reddi et al 2009).…”
mentioning
confidence: 99%
“…Cellular levels of PtdIns-4-P and PtdIns-4,5-P 2 are not affected in hydrolase-deficient strains (40). Indeed, the vacuole/lysosome contains candidate lipases and phosphatases (41,42), which may function in the turn-* This minireview will be reprinted in the 1999 Minireview Compendium, which will be available in December, 1999. This is the second article of five in "A Thematic Series on Kinases and Phosphatases That Regulate Lipid Signaling."…”
Section: Ptdins-3-p Transits Golgi/endosomalmentioning
confidence: 99%